Y-stent-assisted coil embolisation of wide necked aneurysms using a new fully retrievable and detachable intracranial stent: Report of two cases - Muda, Ahmad Sobri; Md Ralib @ Md Raghib, Ahmad Razali; Yaacob, Yazmin; Zakaria, Rozman; Bakar, Azizi Abu (Universiti Sains Malaysia, 2011)
Endovascular treatment of wide-necked aneurysms poses a challenge for the endovascular therapist. The Y-stent--assisted technique has been used for stent-assisted coil embolisation for wide-necked bifurcation aneurysms. This technique has been described for basilar tip aneurysms and middle cerebral artery bifurcation aneurysms using Neuroform and Enterprise stents. We report 2 cases of wide-necked bifurcation aneurysms that were treated with Y-stent--assisted coil embolisation using a new, fully retrievable and detachable intracranial stent (Solitaire ABTM). We describe the advantages of a fully retrievable and detachable stent and its feasibility of forming a Y configuration.